The Effect of Leverage, Profitability, and Investment Opportunity Set on Company Value with Dividend Policy as a Moderating Variable: Study on Non-Financial Companies in 2019-2022 - Ni Ketut Puspita Gayatri; Naniek Noviari (International Journal of Management Research and Economics, 2024)
Corporate value is an important concept for investors in evaluating the overall performance of a company for shareholders and other stakeholders. The value of a company that is proxied to the stock price makes the company try to maximize the value of the company by maximizing the stock market price. The company's value also takes into account external factors that affect the company's performance. These are such as market conditions, industrial competition, and government regulations. The purpose of this study is to determine the influence of leverage, profitability, and investment opportunity set, on the value of companies with dividend policy as a moderator. The population of this study is 719 non-financial companies listed on the Indonesia Stock Exchange in 2019-2022. The selection of samples in this study was carried out using the purposive sampling method so that the number of samples in this study amounted to 204 samples. The data analysis technique uses Moderated Regression Analysis (MRA). The results of the study show that partially the variables of leverage, profitability, and investment opportunity set affect the company's value. Meanwhile, the interaction between the variables of disclosure of leverage, profitability, investment opportunity set and dividend policy variables shows that leverage, profitability, and investment opportunity set are not able to moderate the influence of leverage, profitability, and investment opportunity set on the value of companies in non-financial companies listed on the Indonesia Stock Exchange for the 2019-2022 period.